2013
DOI: 10.1158/0008-5472.can-13-0560
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Pharmacologic Inhibition of mTORC1 Promotes EMT by a TGF-β–Independent Mechanism

Abstract: Epithelial-to-mesenchymal transition (EMT) is a transdifferentiation process that converts epithelial cells into highly motile mesenchymal cells. This physiologic process occurs largely during embryonic development but is aberrantly reactivated in different pathologic situations, including fibrosis and cancer. We conducted a siRNA screening targeted to the human kinome with the aim of discovering new EMT effectors. With this approach, we have identified mTOR complex 1 (mTORC1), a nutrient sensor that controls … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 44 publications
3
36
0
Order By: Relevance
“…However, a more recent study reported conflicting results. Using normal immortalized human epithelial cell lines and primary epithelial cells, Mikaelian and colleagues [40] showed that genetic and pharmacologic inhibition of mTORC1 triggers EMT associated with upregulation of ZEB1, known to activate EMT, but these effects are not found in cancer-driven cell lines including the MDA-MB-231 breast cancer cell line as we used in this study. Indeed, we found that mTORC1 inhibition represses EMT process in colon and breast cancer cells by specific inhibition of Snail translation attendant with increased expression of the epithelial marker E-cadherin, thus suppressing cancer cell migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…However, a more recent study reported conflicting results. Using normal immortalized human epithelial cell lines and primary epithelial cells, Mikaelian and colleagues [40] showed that genetic and pharmacologic inhibition of mTORC1 triggers EMT associated with upregulation of ZEB1, known to activate EMT, but these effects are not found in cancer-driven cell lines including the MDA-MB-231 breast cancer cell line as we used in this study. Indeed, we found that mTORC1 inhibition represses EMT process in colon and breast cancer cells by specific inhibition of Snail translation attendant with increased expression of the epithelial marker E-cadherin, thus suppressing cancer cell migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…et. al [27] have reported that miR-200 miRNAs were involved in the process of mTOR mediated ZEB1 expression, the detailed mechanisms regarding how FBXW7/mTOR regulating ZEB1 expression in CCA need further studies.…”
Section: Discussionmentioning
confidence: 99%
“…45,46 However, mTORC1 was also negatively implicated in the process of EMT. 47 Whether PDK1 regulates the EMT program by activating downstream mTOR needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%